Self-Managing Teams: A Driving Force for Change in Expert Organisations’ Work Culture - Janhunen, Julia (My University, 2024)
Due to the rapid development of the information technology industries, using self-managing teams and agile transformations has increased its popularity across industries. The underlying motivation for implementing agile self-managing teams has been to decrease organisational bureaucracy and increase the organisation's adaptability. However, as the phenomenon has kept expanding to new industries, it has become increasingly important to understand how self-managing teams adopt new ways of working to reach the desired outcomes. This thesis delves into the cultural dynamics of self-managing teams and their transformative potential in the context of organisational change. Given their elevated autonomy and decision-making authority, it is intriguing to explore how these teams embrace new work cultures during an organisational transformation. This research not only contributes to academic discussions but also offers practical insights into the role of self-managing teams in organisational change, the emergence of new work cultures, and the potential variations in team cultures. Given the complex and dynamic social environment in which these teams operate, this study adopts an ethnographic approach. The ethnographic approach involves expert interviews and non-participant observations, allowing for a comprehensive understanding of the diverse work cultures within self-managing teams. The study also employs a multifaceted approach, including high iterations and multiple field visits, to ensure a thorough immersion in the research setting. The empirical evidence showcased the possibility that various factors, such as team structural compositions or previous connections to management, impacted how the team decided to adapt to their new work culture. Depending on the impacting factors, the empirical evidence showed a spectrum of approaches from structured to creative work cultures that the teams had utilised. Hence, variations between work cultures were bound to exist depending on the level of structure that the team had decided to implement.

Tietotekniikkatoimialan nopean kehityksen seurauksena itseohjautuvien tiimien ja ketterien muutosohjelmien jalkauttaminen on lisännyt suosiotaan yli toimialojen. Perimmäisenä motivaationa ketterien itseohjautuvien tiimien käyttöönoton taustalla on ollut organisaatioiden tahto vähentää niiden sisäistä byrokratiaa ja kehittää organisaation sopeutumiskykyä. Kehityksen laajentuessa uusille toimialoille, on tullut tärkeämmäksi ymmärtää, miten itseohjautuvat tiimit päättävät käyttää autonomiaansa uusia työskentelytapojansa suunnitellessa. Tämä tutkielma syventyy itseohjautuvien tiimien muutosvoimaan ja niiden aikaansaamiin työkulttuureihin yrityksen transformaatiossa. Itseohjautuvien tiimien omaavan autonomian vuoksi tutkielma pyrkii kuvaamaan miten tiimit omaksuvat uusia työkulttuureita transformaation aikana. Tutkielma pyrkii myös edistämään akateemista keskustelua sekä tuomaan käytännön näkökulmia aiheesta avaamalla itseohjautuvien tiimien roolia transformaatiossa, miten tiimit omaksuvat uusia työkulttuureita sekä mitä eroja työkulttuureihin voi syntyä. Tutkielman moniuloitteisen ympäristön johdosta tutkielmassa on hyödynnetty etnografista lähestymistapaa haastatellen muutosohjelman asiantuntijaa sekä havainnoimalla tiimejä niiden luontaisessa työympäristössä. Tutkielman menetelmillä pyritään perusteelliseen tutkimusympäristön tarkasteluun toistuvilla kenttätutkimuksilla ja iteratiivisella otteella, jotta tutkielma pystyy kuvaamaan itseohjautuvien tiimien moninaisia työkulttuureita ja dynaamista luonnetta. Tutkielman empiirisestä aineistosta voidaan tunnistaa erilaisia tekijöitä, jotka kuten tiimien rakenteet tai aikaisempi suhde esihenkilöön, jotka vaikuttavat tiimien päätökseen uuden työkulttuurin omaksumisesta. Riippuen vaikuttavista tekijöistä, tiimin työkulttuurin ominaisuudet vaihtelivat niin strukturoidusta työtavoista hyvin luoviin menetelmiin. Näin ollen työkulttuurien muunnelmat olivat väistämättömiä riippuen siitä, kuinka paljon rakenteita tiimi päätti ottaa käyttöön.
Keywords: self-managing teams, agile, transformation, work culture, itseohjautuvat tiimit, muutosohjelma, ketterä, työkulttuuri